2002
DOI: 10.1248/cpb.50.1109
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Activity of Rigid Cannabinoid CB1 Receptor Antagonists.

Abstract: Cannabinoids are present in the Indian hemp Cannabis sativa and have been used as medicinal agents for centuries.1,2) However, only within the past ten years the research in the cannabinoid area has revealed pivotal information on CB receptors and their (endogenous) agonists. The discovery and the subsequent cloning 3,4) of two subtypes of cannabinoid receptor (CB 1 and CB 2 ) stimulated the search for novel cannabinoid antagonists and triggered the development of cannabinoid drugs for the treatment of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 16 publications
2
50
0
Order By: Relevance
“…However, the fact that 2 laboratories molecule. It is interesting to note that the research reported by Stoit et al 13 included in vivo administration of the 3 carbon-bridged compound by intraperitoneal (ip) and oral (po) routes, and the authors reported that no activity was detected, which would be more consistent with a compound that had decreased affi nity as compared with SR141716A. However, it is not clear in their report what measures of pharmacological activity were measured, and as the authors pointed out, the bioavailability of the compounds could be quite different.…”
Section: E669mentioning
confidence: 88%
See 2 more Smart Citations
“…However, the fact that 2 laboratories molecule. It is interesting to note that the research reported by Stoit et al 13 included in vivo administration of the 3 carbon-bridged compound by intraperitoneal (ip) and oral (po) routes, and the authors reported that no activity was detected, which would be more consistent with a compound that had decreased affi nity as compared with SR141716A. However, it is not clear in their report what measures of pharmacological activity were measured, and as the authors pointed out, the bioavailability of the compounds could be quite different.…”
Section: E669mentioning
confidence: 88%
“…It would be interesting to examine additional analogs, such as the one proposed in Figure 6 , to better approximate the structure of SR141716A. The Stoit, 13 Mussinu, 11 and Murineddu 14 , 15 research groups used carbon bridges to reduce the conformational mobility of t 4 ( Figure 7 , Table 1 ). Initially, Stoit et al 13 reported the 3 carbon-bridged compound and found that it had lower affi nity for the CB1R than SR141716A.…”
Section: E666mentioning
confidence: 99%
See 1 more Smart Citation
“…[105][106][107] Worth mentioning are 105 (OL-1302) with a pentyl chain at the phenyl ring, 108 107 (AM251) obtained by replacing the 5-phenyl chloro substituent by iodine which is used as a reference compound in cannabinoid studies, 109 and 108 (SR147778) which reduced food intake in rats. 110 Besides, different groups have reported conformationally restricted analogs of Rimonabant such as 106, 111 110 with nanomolar affinity for the hCB1 receptor, 112 referred also as NESS0327 in another publication 113 and 111. 31 A patent has been filed for the 5-aryloxypyrazole 109, a CB1 antagonist.…”
Section: Hydrazidesmentioning
confidence: 99%
“…They display a wide spectrum of biological activities such as cytotoxic, anticancer agents, [1][2][3][4] as high CB 1 receptors, 5 and have very potent antagonistic activity. 5 Substituted hydrazones are known as one of the most important classes of organic compounds, having analgesic, anticancer, antitumor, anti-inflammatory, antibacterial, and antifungal activities. [6][7][8][9][10][11] In addition, many of the poly-heterocyclic ring systems have several biological activities.…”
Section: Introductionmentioning
confidence: 99%